Pengaruh pemberian ekstrak centella asiatica terhadap kadar gula darah sewaktu tikus (rattus novergicus) model cedera otak traumatik - Nafiisah Nafiisah (Faculty of Medicine, Universitas Andalas, 2023)
Hyperglycemic is common in traumatic brain injury (TBI). Centella asiatica (CA) has antioxidant and antihyperglycemic effects. Objective: To determine the effect of CA on GDS in rat with TBI models. Methods: true experimental design with post test only controlled group design. The study used 35 experimental animals randomly divided into 5 groups. P1 was healthy rat, P2 was sick rat, P3, P4, and P5 were the model group TBI and given CA with dose of 150, 300, and 600 mg/kgbb/day. Administration of CA which was given orally and measurement of GDS levels was done after 7 days of treatment. The statistical test used the One Way ANOVA test, the Post Hoc LSD test. Results: Mean GDS at P1 = 94.78 ± 42.47; P2 = 90.97 ± 06.44; P3 = 110.21 ± 3.70; P4 = 122.35 ± 4.91; and P5 = 128.57 ± 3.90. The One Way ANOVA test results show the fact that there is a statistically significant population (p = 0.000). The results of the LSD Post Hoc Test showed that there was a difference between P1 and P3, P4 and P5; P2 with P3, P4 and P5; P3 to P5. Conclusion: the effect of CA on GDS levels in rat with TBI models